Incidental pulmonary nodules in children: characteristic features and clinical course - Başaran, Ayşen; Başaran, Abdurrahman Erdem; Keven, Ayşe; Elmalı, Aygül; Durmuş, Suzan Yılmaz; Kazlı, Tuba; Kocacık-Uygun, Dilara Fatma; Bingöl, Ayşen (The Turkish Journal of Pediatrics, 2022)
Background. There exists insufficient information about the natural course of incidental pulmonary nodules (IPN) determined on tomography in children. The aim was to determine the characteristic features and factors affecting the course of IPN. Methods. This retrospective study included patients who presented at the Pediatric Pulmonology, Allergy & Immunology Section of Akdeniz University Hospital between January 2014-2020, and were determined with pulmonary nodules on high-resolution computed tomography (HRCT). The patients were separated into two groups as those with a nodule decreased in size or which had disappeared on the follow-up HRCT (Group 1) and those with a nodule which had remained at the same size (Group 2). These two groups were compared in respect to demographic data, nodule size and characteristics, and accompanying findings on HRCT. Results. A total of 177 nodules were determined in the 66 patients included in the study. A follow-up HRCT was taken within mean 16.29±11.38 months in 27 patients. In these patients, 78 nodules were determined on the initial HRCT. On the follow-up, twelve of the nodules were seen to have shrunk or disappeared compared to the initial images, 66 had remained the same size, and none had grown. The mean age of the patients in Group 1 was statistically significantly lower than that of patients in Group 2 (p < 0.001). The rates of an accompanying mosaic attenuation pattern (p < 0.001) on HRCT and subsolid density (p=0.011) of the nodules in Group 1 were statistically significantly higher compared to Group 2 and the rate of calcification content was statistically significantly lower (p=0.002). No suspicious or confirmed malignancy was observed in any case throughout the mean follow-up period of 38.33±16.5 months after the initial HRCT. Conclusions. The young age of patients, subsolid structure of nodules, calcification content and the presence of an accompanying mosaic attenuation pattern on HRCT, could be useful factors in the estimation of size in the follow-up of nodules.
Keywords: HRCT; incidental nodule; pulmonary nodule